A new species of Colpoclypeus Lucchese (Hymenoptera: Eulophidae) from Mexico - Sánchez-García, José Antonio; Pineda, Samuel; Martínez, Ana Mabel; Rebollar-Alviter, Angel; Juárez-Gutiérrez, Ana Celestina; Cruz, Ignacio López; la Salle, John; Figueroa, José Isaac (Zootaxa, 2011)
A new species of Colpoclypeus Lucchese (Hymenoptera: Eulophidae) is described and illustrated. Colpoclypeus michoacanensis Sánchez & Figueroa attacks Argyrotaenia montezumae Walsingham (Lepidoptera: Tortricidae) on blackberry plants. A key is included to separate C. michoacanensis from C. florus (Walker), the only other species in this genus.